Female Workers' Skills, Wages, and Householding in Bangladesh's Readymade Garment Industry: The Case of a Japanese Multinational Company. (January 2020) - Nagata, Hanako
The economic relationship between Japan and Bangladesh has grown stronger since the global financial crisis of 2008, with Bangladesh being identified as 'China plus one' by the Japanese companies. These companies have accordingly begun transferring the capital from China to Bangladesh to avoid political and social risks in China. This article examines the skills, wages, and householding of female Bangladeshi readymade garment workers, focussing on a Japanese multinational company's international transfers and business activities in Bangladesh since the global financial crisis. This study yielded three main findings. First, it identified the structure of the division of labour involved in the production of pairs of short pants exported to Japan. Second, it compared 20 female operators' wage assessments to those of the overall labour force, based on their skills and experience, and pointed out ambiguous and unfounded issues caused by the gender-asymmetrical workforce deployment of Bangladeshi factories. This gender-asymmetrical system is responsible for Bangladeshi female workers' low wages. Finally, despite their low wages, the analyzed Bangladeshi women were found to share multiple household reproduction costs through remittances and perform most of the housework and care work in the household. JEL: B54, F23, F66, O53